Numerical analysis of wind induced response of spar mooring-riser system / Abdulrahman Eyada Ibrahim - Abdulrahman Eyada, Ibrahim (2017)
The search for more sources of energy has become highly urgent given the excessive oil and gas consumption in the 20th century and the depletion of most hydrocarbon reservoirs in the world. In recent decades, the exploitation of hydrocarbon reservoirs under the seas and oceans has been regarded a viable alternative. Several types of floating structures are used in deep water oil and gas production. Spar platforms are the latest type of platforms to be designed and utilized in deep water environments. Coupled behaviour of spar–mooring–riser system under random wave, current and wind loads have been studied using coupled analysis method. This study conducts nonlinear analysis of a spar–mooring–riser system. The spar hull is modelled as a rigid beam element with six degrees of freedom (DOF), with catenary mooring lines and riser pipes treated as hybrid beam elements. The mooring lines are connected to the spar hull at the fairlead on one end and anchored onto the seabed at the other end. In a similar manner, the riser pipe is connected at the spar keel, and its lowest end is hinged to the seabed, which is modelled as a rigid flat surface with a large area capable of mooring contact behaviour simulation. Instantaneous damping and tension fluctuation forces of the mooring–riser system, as well as other properties that vary with time have also been considered. Finite element analysis of the spar–mooring–riser system simulated as a single fully coupled integrated model using the ABAQUS/AQUA code was conducted to obtain system responses under a long crested random wave with and without current and wind inclusion. Some of the obtained results from free vibration, static and dynamic analysis are compared with well–established published experimental results. Time histories, power spectral density functions, and statistical analyses were used in evaluating the system responses. Riser inclusion caused more damping to the coupled spar–mooring–riser system. The maximum values of the surge, heave and pitching motions as well as mooring top tension are decreased by 22.9%, 63.3%, 20.7% and 3.1% respectively. Current load induces a significant shift in the spar position away from its original place in the random sea state in addition to a notable reduction in the heave, pitch and riser top tension responses. The diminishing fluctuation highlights the firmness and controlled oscillations of the spar platform relative to its new mean position. Aerodynamic loading induces greater lateral shifting of the spar hull with 88% due to total hydro – aerodynamic loading with respect to wave and current induced surge while the heave motion reduced by 13.5% for the wind and current inclusion comparing with the case of current only. This fact shows the firmness of the Spar-mooringriser system. The tension fluctuation caused by the wind force does not increased because of the high pretension in mooring system; however, the top tension magnitude of the mooring, riser top tension and Von Mises stress are significantly increased by 4.77%, 27.1% and 26.3% respectively.